Netherlands Antilles : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in the Netherlands Antilles during 1990-96. The economic situation started deteriorating significantly since the early 1990s. Economic growth slackened, mainly reflecting weak investment and a sharp drop in tourist arrivals in 1995-96 owing to hurricane damage. The underlying external position deteriorated progressively, and reserves fell to an uncomfortably low level. The major factors behind the deterioration were occasional slippages in monetary policy and persistently large fiscal deficits that had their roots in a rapid growth of personnel costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet